Azuela, Antonio (2006), Visionarios y pragmáticos. Una aproximación sociológica al derecho ambiental, México, IISUNAM / Fontamara, 537 p. - Ugalde, Vicente (Estudios Demográficos y Urbanos, 2007)
Azuela, Antonio. (2006). Visionarios y pragmáticos. Una aproximación sociológica al derecho ambiental, México, IISUNAM/Fontamara, 537 p.